2012
DOI: 10.1590/s0102-33062012000100008
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de bordas lineares na fenologia de espécies arbóreas zoocóricas em um remanescente de Mata Atlântica

Abstract: (Eff ect of linear edges in the phenology of animal dispersed tree species in a remnant of Atlantic Forest). Th e dispersal of seeds is one of the crucial phases of the life cycle of plants and plant phenology is among the factors that regulate the dispersal mode and activity of dispersers. In landscapes subject to fragmentation, the distribution of dispersal syndromes may be modifi ed due to changes in fl ora composition and structure caused by edge eff ects, which may also change plant phenodynamics. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
2
13
0
6
Order By: Relevance
“…In tropical forests, areas adjacent to linear gaps are characterized by low species richness, high proportion of pioneers and anemochorous plants and presence of exotic species, as reported in this study and others (Ribeiro et al 2009a;Reznik et al 2012;Prieto et al 2014). We also found that pathway width influences the nearby vegetation as much as its presence.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In tropical forests, areas adjacent to linear gaps are characterized by low species richness, high proportion of pioneers and anemochorous plants and presence of exotic species, as reported in this study and others (Ribeiro et al 2009a;Reznik et al 2012;Prieto et al 2014). We also found that pathway width influences the nearby vegetation as much as its presence.…”
Section: Discussionsupporting
confidence: 85%
“…January- March 2017 Several studies addressed the changes in vegetation structure and composition at the edges of linear forest gaps (Demir 2007;Enoki et al 2012;Otto et al 2013;Li et al 2014) and just a few conducted in tropical forests focused on linear gaps caused by roads, gas pipelines and power lines (Reznik et al 2012;Prieto et al 2014;CoutoSantos et al 2015), or pastures (Ribeiro et al 2009a). In those studies, linear gaps aff ected the phenodynamics of animal dispersed plants (Reznik et al 2012), tree species structure and richness (Ribeiro et al 2009a;Couto-Santos et al 2015), and proportion of pioneer species (Prieto et al 2014). However, the extent to which the pathway width aff ects those forest attributes has never been properly assessed and understood.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the influence of edge effects in neotropical forests (Burkey 1993;Laurance et al 1998;Olander et al 1998;Mesquita et al 1999;Paciencia & Prado 2005;Laurance et al 2009;Reznik et al 2012) and reported changes in composition, diversity, and dynamics of species. Nevertheless, other research suggests that edge effects may actually not have serious negative outcomes, exerting positive influences on some variables, or even no influence at all (Oliveira et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Em áreas com sazonalidade acentuada os vegetais apresentam ciclos restritos a determinada estação do ano, revelando dependência do clima (Costa et al 1992;Liebsch & Mikich 2009), ou podem ser contínuos, ocorrendo ao longo do ano (Funch et al 2002;Genini et al 2008). Estudos fenológicos anteriores entre borda e interior revelam a tendência de maior atividade reprodutiva na borda, devido à maior incidência de luz e uma possível diminuição das interações com polinizadores e dispersores (Arberti & Morellato 2010;Reznik et al 2012). Além das condições climáticas, efeitos de borda podem atuar nos vegetais alterando sua atividade fenológica reprodutiva, com consequências para disponibilidade de recursos para polinizadores e frugívoros (Aizen et al 2002;Aguilar et al 2006;Reznik et al 2012;Pires et al 2014).…”
unclassified
“…Estudos fenológicos anteriores entre borda e interior revelam a tendência de maior atividade reprodutiva na borda, devido à maior incidência de luz e uma possível diminuição das interações com polinizadores e dispersores (Arberti & Morellato 2010;Reznik et al 2012). Além das condições climáticas, efeitos de borda podem atuar nos vegetais alterando sua atividade fenológica reprodutiva, com consequências para disponibilidade de recursos para polinizadores e frugívoros (Aizen et al 2002;Aguilar et al 2006;Reznik et al 2012;Pires et al 2014).…”
unclassified